Riemannove ničle in praštevila - Simonič, Aleksander (Obzornik za matematiko in fiziko, 2017)
We prove not so well-known E. Landau's formula, which connects the summation of terms ?$x^ρ$? over nontrivial zeros ?$ρ$? of the Riemann zeta function with the von Mangoldt function ?$Λ(x)$?. This formula simply illustrates the principle that nontrivial zeros determine prime numbers.
Keywords: netrivialne ničle; praštevila; Riemannova funkcija zeta; von Mangoldtova funkcija